An Analysis Of Directive Speech Act In Indonesian Novels - Fatimah, Siti; Andika, Alek (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
Literary aesthetics plays a central role in understanding the artistic value of the novel. Contemporary Indonesian novels demonstrate dynamic developments in themes, ideologies, formal exploration, and language, offering a multi-layered aesthetic experience. This study employs a multidisciplinary approach encompassing stylistics, narrative structure, intertextuality, and philosophy to appreciate the work as a complete artistic entity. The research aims to develop an integrative literary aesthetic analysis model for contemporary Indonesian novels, designing a framework that integrates four dimensions: language and style, theme and values, form and structure, as well as intertextuality and context; applying it to representative novels; and identifying patterns of interaction among these dimensions in constructing the work’s aesthetic integrity. The methodology employs a Systematic Literature Review (SLR), a structured and systematic approach to identifying, evaluating, and synthesizing empirical evidence relevant to the research questions. The SLR provides a comprehensive and unbiased summary of the scientific literature, yielding robust conclusions based on credible evidence for a deep understanding of a specific phenomenon or topic. The discussion covers four categories: the aesthetics of language and narrative style, which emphasizes the role of figurative language, imagery, poetic diction, and captivating narrative techniques in evoking emotions and creating atmosphere; the aesthetics of theme and values, which analyzes the depth of themes such as love, spirituality, and social criticism, as well as the coherence between themes and events and the conveyance of universal values; the aesthetics of narrative form and structure, which explores innovations in story architecture through genre blending and theoretical frameworks; and the intertextual-contextual aesthetics, which reveals the work’s dialogue with other texts and its socio-cultural context, creating complex layers of meaning and critical-reflective beauty. This study concludes that the richness of figurative language, imagery, and narrative techniques form the primary foundation that evokes readers’ sensory-emotional experiences; the depth of themes and universal values constitute the soul of the narrative that provides emotional resonance; narrative architecture innovation determines artistic strength through the harmony of form and content; and the beauty of contemporary literature is dialogic in nature, enriched by its relationship with other texts and socio-historical contexts, thereby creating a critical-reflective aesthetic.